2005
DOI: 10.1016/j.jenvman.2005.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting environmental equity: Air quality responses to road user charging in Leeds, UK

Abstract: Sustainable development requires that the goals of economic development, environmental protection and social justice are considered collectively when formulating development strategies. In the context of planning sustainable transport systems, trade-offs between the economy and the environment, and between the economy and social justice have received considerable attention. In contrast, much less attention has been paid to environmental equity,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 21 publications
(30 reference statements)
1
27
0
Order By: Relevance
“…Similar results have also been obtained in Canada (Carrier et al 2014;Jerrett et al 2007;Sider et al, 2013), the United Kingdom (Briggs, Abellan, and Fecht 2008;Mitchell 2005;Mitchell and Dorling 2003), New Zealand (Kingham, Pearce, and Zawar-Reza 2007), Germany (Schikowski et al 2008), Finland (Rotko et al 1999), France (Havard et al 2009) and Norway (Naess et al 2007). However, the link between air pollutant levels and the distribution of ethnic or racial groups seems to be less clear, and tends to vary in different geographic contexts (Pastor, Sadd, and Hipp 2001;Ringquist 1997) Grineski et al (2015) and Chakraborty et al (2014) also found that neighborhoods in Houston characterized by a higher presence of Hispanic residents and a lower percentage of homeowners faced a significantly greater exposure to both chronic and acute pollution risks.…”
Section: Environmental Nuisancessupporting
confidence: 69%
“…Similar results have also been obtained in Canada (Carrier et al 2014;Jerrett et al 2007;Sider et al, 2013), the United Kingdom (Briggs, Abellan, and Fecht 2008;Mitchell 2005;Mitchell and Dorling 2003), New Zealand (Kingham, Pearce, and Zawar-Reza 2007), Germany (Schikowski et al 2008), Finland (Rotko et al 1999), France (Havard et al 2009) and Norway (Naess et al 2007). However, the link between air pollutant levels and the distribution of ethnic or racial groups seems to be less clear, and tends to vary in different geographic contexts (Pastor, Sadd, and Hipp 2001;Ringquist 1997) Grineski et al (2015) and Chakraborty et al (2014) also found that neighborhoods in Houston characterized by a higher presence of Hispanic residents and a lower percentage of homeowners faced a significantly greater exposure to both chronic and acute pollution risks.…”
Section: Environmental Nuisancessupporting
confidence: 69%
“…This could be in the form of increased parking charges at destination or fuel tax levies (a 10% increase in fuel prices usually results in a 1-3% decline in travel; IEA, 2002;Anable and Boardman, 2005). Other options include road tolling or distance based charging based on Global Positioning System technology (Mitchell, 2005), where motorists are charged on vehicle use depending on the route taken and the time of day. Opponents to the scheme believe that such systems will be difficult and expensive to introduce and will offer no significant carbon reductions (Anable and Boardman, 2005).…”
Section: Car Mitigationsmentioning
confidence: 99%
“…Still, monitoring of the road and warranty are mostly related to functionality of the road rather then it 'greenness'. And even in cases where environmentrelated requirements are mentioned in procurement projects, in practice they are not always met or are evaluated as part of the quality assurance control [9].…”
Section: A Sq1: Traditional Procurementmentioning
confidence: 99%